The distribution of discrimination in immigrant earnings - evidence from Britain 1974-1993 - Kevin Denny; Colm Harmon; Maurice Roche (Institute for Fiscal Studies (IFS), 1997)
This paper uses the General Household Survey data for the UK to study earnings discrimination between natives and migrants. The key result is that the main source of discrimination is ethnicity rather than migrant status per se. This paper differs from the conventional focus in studies of earnings discrimination, which focus on mean wage differences. In contrast we study the entire distribution of the wage gap, and incorporate distributionally sensitive measures of the wage gap reflecting different levels of aversion to discrimination. Our results are consistent with previous studies for the UK that find that non-white immigrants are the most widely discriminated in terms of their labour market returns. Moreover this discrimination on the basis of colour is also present in the sub-sample of natives.
Keywords: 330